The Problem of Ownership of Land Rights is Reviewed Based on the Law and Government Regulations - Miptahuddin, Cecep (Sahabat Publikasi, 2024)
The issue of land rights ownership is intricate and multifaceted, particularly within the realm of agricultural law in Indonesia. This article delves into and scrutinizes various problems related to land rights ownership, emphasizing the legal framework established by the Basic Agrarian Law (UUPA) and relevant government regulations. Utilizing document analysis and literature review as research methods, the study examines a variety of cases, related research, and pertinent legal texts. The analysis uncovers several issues, such as land rights conflicts, ambiguities in legal interpretation, administrative hurdles, and challenges in practical implementation. The research identifies several root causes of these problems, including the disparity between formal law and informal practices, as well as a need for more awareness regarding rights and obligations concerning land ownership. In conclusion, the article underscores the necessity for concrete measures to address these issues, such as legal reforms, heightened public awareness, and enhancements to the land administration system to foster justice and legal certainty for all stakeholders.